1972
DOI: 10.1021/jf60182a015
|View full text |Cite
|
Sign up to set email alerts
|

Thermally produced flavor components in the aroma of meat and poultry

Abstract: Meat flavor (taste and aroma) is developed by heating the raw product. Thermal degradation of the many classes of chemical compounds in meat results in flavor formation. Conditions influencing the chemical composition of meat, heating procedures, and products formed on heating various meat components are reviewed. None of the compounds identified in meat aroma has been described as uniquely meaty. Recent identifications of interesting boiled beef flavor fractions, however, suggest that progress in elucidating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0
3

Year Published

1977
1977
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 34 publications
0
45
0
3
Order By: Relevance
“…The small differences observed between the broth at 85°C and 95°C may be attributed to different components (such as sugars) and amino acids reactions (Maillard-type) made possible at higher heating temperatures (Bailey, 1988;Bowers et al, 1987). Wasserman (1972) reported that browning began at about 90°C and increased with time and temperature. It was also observed that peptides and amino acids were formed and removed during processing of cooked principles and/or precursors for the formation of Maillard prodand stored meat by Spanier et al, 1988.…”
Section: Results and Discussion Sensory Evaluation And Analytical Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The small differences observed between the broth at 85°C and 95°C may be attributed to different components (such as sugars) and amino acids reactions (Maillard-type) made possible at higher heating temperatures (Bailey, 1988;Bowers et al, 1987). Wasserman (1972) reported that browning began at about 90°C and increased with time and temperature. It was also observed that peptides and amino acids were formed and removed during processing of cooked principles and/or precursors for the formation of Maillard prodand stored meat by Spanier et al, 1988.…”
Section: Results and Discussion Sensory Evaluation And Analytical Datamentioning
confidence: 99%
“…myofibrillar protein (Wasserman, 1972). Cheng and Parrish (1979) studied heat-induced changes in myofibrillar protein solubility and as Wasserman (1972) reported most of the proteins are coagulated between 55°C and 80°C. Spanier et al (1990) studied the activity of some hydrolytic enzymes in beef at temperatures similar to those during cooking.…”
Section: Introductionmentioning
confidence: 99%
“…Its aroma resembles blood serum (Wasserman, 1972; Joo and Kim, 2011). However, significant changes take place in the flavour of meat during cooking.…”
Section: General Chemistry Of Chicken Meat Flavourmentioning
confidence: 99%
“…Generally, raw meat has a bloody, metallic, salty taste, with an aroma resembling blood serum (Wasserman, 1972). The Maillard reaction, the thermal degradation of lipids and Maillard-lipid interactions are considered to be the main reactions, which result in flavour and aroma compounds during cooking (Brunton et al, 2002).…”
Section: Chemistry Of Cooked Chicken Meat Flavourmentioning
confidence: 99%